PERKEMBANGAN PSIKOLOGI ANAK DALAM KONTEKS PEMBELAJARAN - Sintya Kartika Prameswari; Safira Aulia Rahma; Muhammad Wazir Zuamaul Haq (JIP: Jurnal Ilmu Pendidikan, 2025)
The psychological development of children is the focus of this research. This development is a vital foundation for the learning process because it encompasses the cognitive, emotional, social, and moral aspects that influence children's capacity to comprehend and absorb subject matter. In the context of education, it is crucial for teachers to understand the stages of children's psychological development in order to design learning strategies that suit their characteristics and needs. This study examines the dynamics of children's psychological development from elementary school age to early adolescence, focusing on its impact on motivation, social interactions in the classroom, and potential development. Using a developmental and educational psychology approach, this paper emphasizes the importance of teachers' roles and responsive learning environments in supporting children's optimal growth and development. The researcher employed a library research method, a qualitative approach focusing on collecting data from literature sources such as books, journals, and articles discussing child psychology development. The results of the study show that learning that pays attention to children's psychological aspects will be more effective in improving learning outcomes and fostering positive character.